A Relationship of Project Management Process Factors with SMEs Performance - Alshehhi, Abdulnaser; Kasim, Rozilah (International Journal of Sustainable Construction Engineering and Technology, 2020)
Main problems of SMEs in UAE are lack of talented and experienced people and funding difficulties. Beside that the prevailing negative economic outlook also affecting SMEs. Several studies found that SMEs are reluctant to apply project management technique due to lack of talent, this paper present a study to connect project management process with SMEs performance in the UAE. A structural model on the relationship between project management factors with SMEs performance was developed and validated. Data used for this modelling was from the questionnaire survey involved 260 respondents from the SMEs employees. The results presented four measurement models of project management process factors that affecting the SMEs in UAE. All the measurement models had undergone evaluation using CFA analysis in AMOS software and found that the models had achieved the acceptable level of fitness. Then these models were tied up into structural model. The evaluation of the structural model was done using path analysis of the software. The results of the structural model indicated that all the hypotheses are significant. It can be concluded that all the four project management processes factors which are scope, cost, communication and risk are significantly can affect the SMEs performance in UAE.